2019
DOI: 10.1371/journal.pone.0216619
|View full text |Cite
|
Sign up to set email alerts
|

Chronotype mediates gender differences in risk propensity and risk-taking

Abstract: Risk-taking is a complex form of decision-making that involves calculated assessments of potential costs and rewards that may be immediate or delayed. Thus, making predictions about inter-individual variation in risk-taking due to personality traits, decision styles or other attributes can be difficult. The association of risk-taking with gender is well-supported; males report higher propensity for risk-taking and show higher risk-taking on tasks measuring actual risk-taking behavior. Risk-taking also appears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 54 publications
0
20
0
Order By: Relevance
“…Both gender-specific and chronotype differences exist, since males report higher propensity for risk-taking, in particular E-types. However, although there is no significant difference in risk propensity or risk-taking behaviour across chronotypes in males, E-type females significantly report and take more risk than other chronotypes [39].…”
Section: Discussionmentioning
confidence: 70%
“…Both gender-specific and chronotype differences exist, since males report higher propensity for risk-taking, in particular E-types. However, although there is no significant difference in risk propensity or risk-taking behaviour across chronotypes in males, E-type females significantly report and take more risk than other chronotypes [39].…”
Section: Discussionmentioning
confidence: 70%
“…This has been shown in healthy young adults (Kang et al 2015) and in a sample aged 20-70 y, with impulsivity mediating an observed relationship between eveningness (from MEQ) and anger (Hwang et al 2016). A relationship between eveningness (from MEQ) and self-reported risk propensity has also been shown in young adults (Gowen et al 2019); Wang and Chartrand (2015) linked eveningness to greater selfreported financial risk-taking in an adult sample aged 18 to 69 y. Thus, links between eveningness and subjective impulsivity appear to be robust.…”
Section: Introductionmentioning
confidence: 72%
“…Previous studies that have investigated risky decisionmaking found that young adult evening types have a greater propensity for risk-taking, as measured using self-report scales (such as the DOSPERT that questions likelihood to engage in risky activities across various domains) (Killgore 2007;Wang and Chartrand 2015). However, associations are less robust when risk-taking tasks (specifically the Balloon Analog Risk Task, BART) are employed; one study found an effect (Gowen et al 2019), whereas others have not (Ingram et al 2016;Killgore 2007). The effects seen here with the temporal discounting task are interesting in this context.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences have appeared on the Domain-Specific Risk-Taking Scale (DOSPERT; Blais and Weber, 2006), a measure and one of the most effective clinical instruments for assessing the tendency to make risky decisions across real-life domains (ethical, health, recreational, social, and financial;Harrison et al, 2005). Researchers have demonstrated that sex predicts risk-taking (e.g., Gowen et al, 2019). Specifically, men make more risky decisions in all domains except the social domain in which women make more risky decisions (e.g., Blais and Weber, 2006;Lozano et al, 2017;Morgenroth et al, 2018).…”
Section: Femininity Fear Of Negative Evaluation and Risk-takingmentioning
confidence: 99%